Implementasi Standar Isi, Standar Proses, Standar Lulusan Sebagai Standar Mutu pendidikan MTs Negeri Di kabupaten Tulungagung: Implementation of Content Standards, Process Standards, Graduate Standards as Quality Standards for State MTs Education in Tulungagung District - Ikhwan, Wahid Khoirul (Universitas Muhammadiyah Sidoarjo, 2015)
Government issued Government Regulation No.19/2005 on National Education Standards. National Education Standards consists of 8 components: (1) Content Standards, (2) Standard Process, (3) Competency Standards, (4) Teachers and Education Personnel Standards, (5) Standards for Infrastructure, (6) Management Standards, (7) Standard Financing, and (8) Educational Assessment Standards. The results content standards, process standards and competency standards (SKL), MTsN in Tulungagung also meets national standards, so that the quality of education in schools MTsN Tulungagung could be better. It can be seen from the following observations sebyai; standard contents index average of 3.7, the standard index averaged 3.3 and 3.7 index competency standards.